The use of bonewax to control massive presacral bleeding - YEGEN, ŞEVKET CUMHUR (SPRINGER-VERLAG, 2002)
Massive presacral bleeding during retroperitoneal resection is unusual, and can be difficult to control. We describe a technique for managing this complication whereby bonewax is pushed through the presacral fascia and periosteum directly into the bleeding point in the sacrum, followed by abdominal packing. This maneuver proved successful for achieving hemostasis when we recently encountered this intraoperative complication.
Keywords: presacral bleeding; bonewax; abdominal packing